Body Weight and Blood Biochemical Changes Following Nutritional Supplementation in Prepubertal Jaffrabadi Buffalo (Bubalus bubalis) Heifers - Raval, RJ; Vala, KB; Kalariya, VK; Dhami, AJ; Kavani, FS (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
The high plan of nutrition right from an early age is believed to enhance ovarian activity and early onset of puberty in heifers. This study was therefore conducted to know the body weight, ovarian and blood biochemical changes in nutritionally supplemented and control groups of prepubertal Jaffrabadi buffalo (Bubalus bubalis) heifers. A total of 12 animals of 30 ± 2 month’s age and the identical body weight of 380–410 kg from Cattle Breeding Farm, JAU, Junagadh were utilized for this study. They were randomly divided into two equal groups of 6 animals in each treatment and control groups. The heifers of the treatment group were supplemented with bypass fat (100 g), bypass protein (950 g) and chelated mineral mixture (50 g) over the routine farm feeding practices of control group, and its effect on body weight gain and blood biochemical profiles were studied at a monthly interval during 6 months of experimental period. The overall effect of nutritional supplementation on animals body weight, blood glucose and total cholesterol over the control group was statistically non-significant (p >0.05) yet beneficial. The plasma total protein levels in the supplemented group increased with a duration of supplement and levels were significantly (p <0.05) higher over the control group. The ovarian dynamics evaluated by transrectal ultrasound during last three months of the study revealed an increasing number of growing follicles >4 mm in diameters (5.00 ± 0.13 to 6.67 ± 0.40), without significant variation in diameters of largest follicles (9.14 ± 0.45 to 10.27 ± 0.85 mm) between groups or periods. However, none of the heifers exhibited behavioral signs of estrus during 6 months study, in spite of the establishment of cyclicity with the presence of developed follicles, or CLs suggesting silent ovulation, at 36 ± 2 months of age in this breed.